Solubility of the nonlinear Valle Pussen problems - Dementiev , S. N.; Yanovsky , L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We consider the solvability of a boundary-value problem of form (1), (2) in the class of nonlinearities of f, for which the traditional restrictions of the Lifschitz-conditions type are replaced by concavity (or generalized concavity) conditions with respect to specially chosen variables.